The Influence of Training, Rewards, and Work Motivation on Employee Performance(A Study of Employees at the Petamburan II Urban Village, Central Jakarta) - Muhammad Faiz (Jurnal Multidisiplin, 2026)
The purpose of this study was to investigate the effect of Training, Rewards, and Work Motivation on Employee Performance in Petamburan II Subdistrict, Central Jakarta. Using a Likert-scale questionnaire, the study involved a sample of 62 employees using a non-probability sampling method and saturated sampling technique. The results of a multiple linear regression analysis in SPSS v.26 indicate that Training has a significant positive effect and Rewards have no significant effect on Employee Performance, while Work Motivation has a significant positive effect. These findings provide insights for management in managing Training and Rewards and improving supportive Work Motivation, with practical implications for improving employee well-being and organizational effectiveness. These findings also provide recommendations for further research in this area.